2020
DOI: 10.1038/s41419-020-02877-0
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CDKN2B-AS1/miR-141/cyclin D network regulates tumor progression and metastasis of renal cell carcinoma

Abstract: The molecular heterogeneity of renal cell carcinoma (RCC) complicates the therapeutic interventions for advanced metastatic disease and thus its management remains a significant challenge. This study investigates the role of the lncRNA CDKN2B-AS1 and miR-141-3p interactions in the progression and metastasis of kidney cancer. Human renal cancer cell lines (ACHN and Caki1), normal RPTEC cells, tissue cohorts, and a series of in vitro assays and in vivo mouse model were used for this study. An overexpression of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 52 publications
(66 reference statements)
4
42
0
Order By: Relevance
“…In addition, we further verified the effects of CDKN2B-AS1 on KIRC carcinogenesis in vivo and confirmed its prognostic capability by multivariate analysis. Hence, our findings, together with those of other studies 22 , 23 , indicate that CDKN2B-AS1 drives the malignancy of KIRC in vitro and in vivo, and has the potential to serve as an independent prognostic factor for worse KIRC progression.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In addition, we further verified the effects of CDKN2B-AS1 on KIRC carcinogenesis in vivo and confirmed its prognostic capability by multivariate analysis. Hence, our findings, together with those of other studies 22 , 23 , indicate that CDKN2B-AS1 drives the malignancy of KIRC in vitro and in vivo, and has the potential to serve as an independent prognostic factor for worse KIRC progression.…”
Section: Discussionsupporting
confidence: 81%
“…However, lncRNAs located in the nucleus can participate in the gene regulation at the chromatin modification and gene transcription levels 36 . Although the latest study 23 showed that CDKN2B-AS1 can function as a ceRNA to regulate cyclin-D1/D2 expression, resulting in RCC aggressiveness, by using cell cytoplasm/nuclear fractionation assays, we found that CDKN2B-AS1 is mainly localized in the nucleus, as in previous reports on other tumors 30 , 37 , 38 , and indicating that CDKN2B-AS1 might regulate NUF2 expression via a transcriptional mechanism. Since CDKN2B-AS1 was reported to cooperate with chromatin-modifying enzymes CBX7/PRC1 or SUZ12/PRC2, it affects histone H3K27me3 enrichment in the promoter region, thus activating epigenetic activation or gene silencing 37 , 39 .…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“… 6 Recently, numerous lncRNAs have been identified in humans and other organisms that play diverse roles in regulating various phenomenon, such as cell proliferation and apoptosis, 7 , 8 cell development, 9 cell differentiation, 10 and development of certain diseases. 11 , 12 Specifically, lncRNAs are involved in regulating spermatogenesis, 13 , 14 steroidogenesis, 15 embryo implantation 16 and development, 17 follicular development, 18 oocyte maturation, 19 GC apoptosis and proliferation, 20 , 21 and reproductive diseases, 22 , 23 suggesting their importance in reproduction. 24 However, only a few lncRNAs have been identified in domestic animals.…”
Section: Introductionmentioning
confidence: 99%